Molecular weight and molar substitution are more important in HES-induced renal impairment than concentration after hemorrhagic and septic shock - Simon, T P; Thiele, C; Schuerholz, T; Fries, M; Stadermann, F; Haase, G; Amann, Kerstin Ute; Marx, G (Minerva Anestesiologica, 2015)
Clinical studies have raised concerns about the safety of 6% hydroxyethylstarch (HES) 130/0.42, but the pathomechanisms of this renal impairment remain unknown. To evaluate the effects of different HES concentrations, molar substitutions and molecular weights in HES-induced renal impairment, we used a porcine two-hit model that combined haemorrhagic and septic shock.We conducted a prospective, randomised, double-blinded, controlled study in a university animal laboratory. Thirty anaesthetised and ventilated pigs were randomised to receive volume replacement therapy using 6% HES130/0.42, 6% HES200/0.5, 10% HES130/0.42 or 10% HES200/0.5, all dissolved in 0.9% NaCl rather than 0.9% NaCl alone. First, we bled the animals until they reached half of their baseline mean arterial pressure (MAP) for 45 minutes followed by fluid resuscitation. As a second hit, sepsis was induced using an Escherichia coli-laden clot 6 hours after haemorrhagic shock. Volume resuscitation started with a delay of two hours and a central venous pressure goal of 12 mmHg.At the end of the study, the groups showed no difference in cardiac output or MAP, but the volume balance (mL/kg BW) was significantly higher in the 0.9% NaCl group (346±90; P<=0.05) than in the other groups (6% HES130, 125±26; 6% HES200, 105±15; 10% HES130, 114±17; 10% HES200, 96±23). Creatinine clearance (mL/min) was significantly lower in the 6% HES200 (26±33) and 10% HES200 (15±18) groups compared to the 0.9% NaCl group (104±46; P<=0.05) but not in the HES 130 formulations (6% HES130: 64±51; 10% HES130: 58±38) at the end of the study.In this porcine two-hit shock model, treatment with 0.9% NaCl, HES 130/0.42 or HES 200/0.5 led to a similar maintenance of haemodynamic values. Despite this similar maintenance of the haemodynamic values, volume replacement with 6% and 10% HES 200/0.5 led to an accumulation of HES, higher colloid osmotic pressure and significantly reduced renal function after haemorrhagic and septic shock. These facts support the presumption that not the concentration but the degree of substitution and the molecular weight play a decisive role in HES-induced renal impairment.
EVALuna2:25475